Diagnosis Molekul Ovalositosis Dan Kaitannya Dengan Haplotipe Globin-B = Molecular Diagnosis Of Ovalocytosis And Its Relation With B-Globin Haplotypes - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Ovalocytosis is genetic trait commonly found in malaria endemic areas, hereditary in nature with oval-shaped red cells. The Molecular basis of SAO is a 27 by deletion in the gene of protein band-3 erythrocyte membrane. This genetic trait with one type of mutation, is widely found among the South East Asian and Oceanean populations including Indonesians. However, little is known whether this 27-bp deletion of band-3 protein gene in Indonesia is identical with those reported in previous studies. Despite similarity of the mutation its origin in various population stocks is still unknown. Using the 0-globin cluster haplotypes which had been used to study the genetic relationship on Indonesian populations, in this particular study, 13 - globin haplotypes distribution in ovalocytosis subjects may help to elucidate the origin of this ovalocytosis mutant. In the previous study it was found that the oval-shaped red cells were prevalence in Alor (Australomelanesians), Sumba (Australomelanesians and Mongoloid) and Sumbawa (Mongoloid). Thirty-two DNA samples from these three populations were amplified using PCR (Polymerase Chain Reaction) with OVFI098/OVR1272 specific primers. The 13-globin cluster haplotypes were determined by digestion of the I-VIII restriction site obtained from PCR amplification product employing the appropriate restriction enzymes. It was found that twenty-eight samples revealed twi narrowly separated bands of 175 by and 148 by sizes representing heterozigous form of ovalocytosis. Meanwhile, the other four samples showed a band with 175 by size representing normal individual. Sequence analysis of the amplified product revealed that the smaller amplified product i.e 148 by had a deletion of 27-bp. The same position of 27-bp deletion in defferent populations suggests that this ovalocytosis is a mutant of band-3 protein with similar nine amino acid deletion as reported in other countries. Observation on 13-globin haplotypes demonstrated that the combination of + was common in Sumbawa, + and +---+- in Sumba and a more complex combinations was observed among individuals from Alor. The most common framework in those three populations were +- and --. The observation of idential 13-globin haplotypes in ovalocyosis individuals of these three populations indicates that the ovalocytosis mutant must have been in existence since the early settlement of Australomelanesians in Indonesia, long before the latter population migrations, and spread as an advantage in malaria endemic environment.